Electrical conductivity, photoconductivity, and optical properties of poly(1,4-diaminoanthraquinone) organic semiconductor for optoelectronic applications - Yakuphanoğlu, Fahrettin; Senkal, B. Filiz (Wiley, 2008)
The electrical conductivity and optical properties of the poly(1,4-diaminoanthraquinone) [poly(1,4-DAAQ)] have been investigated. The electrical conductivity of the polymer increases with temperature and room temperature conductivity was found to be 2.68 10(-5) S cm(-1). The optical band gap of the polymer is 1.87 eV due to the direct optical transitions. The photoconductivity of the polymer is higher than that of dark conductivity. When the light is switched on, the resistance decreases abruptly and when it is switched off, the resistance increases. This confirms that the polymer is a photoconductive material. The obtained results indicate that the poly(1,4-DAAQ) is a photoconducting organic semiconductor with photovoltaic and dark current properties. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: organic serniconcluctor; poly(1,4-diaminoanthraquinone); photoconductivity